Covid-19: The last call for telepsychiatry - Amerio, Andrea; Odone, Anna; Marzano, Lisa; Costanza, Alessandra; Aguglia, Andrea; Serafini, Gianluca; Signorelli, Carlo; Ghaemi, S. Nassir; Amore, Mario (Acta Biomedica Atenei Parmensis, 2020)
Not required